Eco-innovative sound absorbing materials from household waste: a project-based learning approach to enhance ecopreneurship skills - Af'idah, Noer; Rochim, Roudhoutul Aulia; Falah, Fajrul; Manasikana, Oktaffi Arinna; Wijayadi, Andri Wahyu; Hayati, Nur; Kuswanti, Nur (Prodi Pendidikan Fisika Universitas Sarjanawiyata Tamansiswa, 2025)
se pollution and household waste accumulation are interrelated environmental challenges that demand sustainable and innovative solutions. This study aimed to develop eco-friendly sound-absorbing materials from household waste through a Project-Based Learning (PjBL) approach to enhance students’ ecopreneurship skills. The research employed a developmental design involving 16 students from the Science Education Study Program at Universitas Hasyim Asy’ari enrolled in the Environmental Science course. The project-based approach comprised problem identification, project design, product fabrication and testing, reflection, and presentation. Data were collected through observations of project implementation, Noise Reduction Coefficient (NRC) measurements, and ecopreneurship skill questionnaires. Results showed that the project was effectively implemented (88.40%), and the developed sound absorber composed of recycled paper, wood dust, and textile waste achieved a maximum NRC of 0.83 at mid-to-high frequencies, indicating good acoustic performance. A paired-sample t-test revealed a statistically significant improvement in students’ ecopreneurship skills (t(15) = 6.21, p < 0.001), especially in sustainability orientation and creative innovation. The project-based activities also helped students better understand the physics of sound absorption and its real-world applications. These findings demonstrate that integrating project-based learning with environmental contexts strengthens physics education while fostering sustainable innovation and green entrepreneurial competence.